Environmental chemistry: Fundamentals - Ibanez, J. G.; Hernandez-Esparza, Margarita; Doria-Serrano, Carmen; Fregoso-Infante, Arturo; Singh, Mono Mohan (Springer, 2010)
Summary: Our Earth is a remarkable reaction vessel. It is of paramount importance that students grow in their understanding and awareness of the astounding effects that chemistry and biochemistry have on our environment. The first book in the field to encompass theory and practice, Environmental Chemistry: Fundamentals covers the chemical and biochemical processes that take place in air, water, soil, and living systems. The text is written with advanced college students in mind; nevertheless, issues are frequently presented in such a way that graduate students and professionals can find subjects of interest. Available separately, an experimental companion book, Environmental Chemistry: Microscale Laboratory Experiments, provides students with a thorough practical introduction to environmental experimentation. By using literature data in many of the examples and problems, both Environmental Chemistry: Fundamentals and Environmental Chemistry: Microscale Laboratory Experiments help students expand their problem solving skills and practice with real situations.